2016
DOI: 10.1002/ijc.29999
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic miR‐126 is a potential plasma biomarker for detection of hepatitis B virus infected hepatocellular carcinoma

Abstract: Controversies about the origin of circulating miRNAs have encouraged us to identify organ specific circulating miRNAs as disease biomarkers. To identify liver-specific miRNAs for hepatocellular carcinoma (HCC), global expression profiling of miRNAs in liver tissue of HBV-HCC and HBV-control with no or mild fibrosis was evaluated. A total of 40 differentially expressed miRNAs were identified in HCC. Among ten highly altered miRNAs, six miRNAs were successfully validated in tissues, whereas only two miRNAs, miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 49 publications
1
28
0
1
Order By: Relevance
“…In contrast, several previous studies found significant dysregulation of miR-30c, [21,53] miR-30b [21] and miR-126 [54,55] in HCC tumor tissue and blood samples, suggesting their potential etiologic or diagnostic roles. However, none of those previous studies used global mean of miRNAs as the normalizer and did not evaluate miRNAs expression stabilities that might lead to false positive findings.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast, several previous studies found significant dysregulation of miR-30c, [21,53] miR-30b [21] and miR-126 [54,55] in HCC tumor tissue and blood samples, suggesting their potential etiologic or diagnostic roles. However, none of those previous studies used global mean of miRNAs as the normalizer and did not evaluate miRNAs expression stabilities that might lead to false positive findings.…”
Section: Discussionmentioning
confidence: 61%
“…Serum anti-SF3B1 autoantibody is a potential diagnostic marker for HCC patients (Hwang et al, 2018). Reportedly, HSPH1 (Yang et al, 2015), APC2 (Ghosh et al, 2016), CHST4 (Gao et al, 2015), HGF (Unic et al, 2018), MTHFD2 (Liu et al, 2016), and AGO3 (Kitagawa et al, 2013) are closely related to HCC.…”
Section: Discussionmentioning
confidence: 99%
“…These include, but are not limited to: DCP [37,38], Glypican-3 [39], fucosylated serum paraoxonase 1 [40] and alpha-1 acid glycoprotein [41], TEMs [42], Dickkopf-1 [43] and EpCam stained circulating tumor cells [44] and staining of HCCs [45], C-reactive protein [46], alpha-L-fucosidase [47] and hepatic miRs [48]. With such a high percent of small and large HCCs having low AFP levels, novel biomarkers are clearly needed.…”
Section: Discussionmentioning
confidence: 99%